Wuji Wan Formula Ameliorates Diarrhea and Disordered Colonic Motility in Post-inflammation Irritable Bowel Syndrome Rats by Modulating the Gut Microbiota - Chen, Ying; Xiao, Shuiming; Gong, Zipeng; Zhu, Xiaoxin; Yang, Qing; Li, Yujie; Gao, Shuangrong; Dong, Yu; Shi, Zhe; Wang, Yajie; Weng, Xiaogang; Li, Qi; et al. (Frontiers in Microbiology, 2017)
Emerging evidence suggests that gut microbiota contribute to the treatment of post-inflammatory irritable bowel syndrome (PI-IBS). Our previous studies have demonstrated that a Chinese formula, Wuji Wan, has the ability to mitigate abdominal pain and diarrhoea in PI-IBS rats. However, little is known about the underlying mechanism and whether the gut microbiota mediate the effect of Wuji Wan on PI-IBS. Thus, the aim of this study was to determine whether Wuji Wan mitigated PI-IBS by modifying the gut microbiota. PI-IBS was induced in Sprague-Dawley rats by enema using 4% acetic acid and restraint stress. Rats were fed water, Wuji Wan extract (630 mg/kg) or pinaverium bromide (13.5 mg/kg). Our data showed that Wuji Wan effectively ameliorated abdominal pain, colonic motility abnormality and visceral hypersensitivity. Analysis of the faecal microbiota showed that Wuji Wan could reverse the reduction in richness of the gut microbiota and significantly increase the relative abundances of Akkermansia, Bacteroides, and Parasutterella; however, Lactobacillus and Prevotella were markedly decreased in the PI-IBS rats. Moreover, Wuji Wan promoted goblet cell proliferation in the colonic mucosa by increasing the release of mucin, up-regulating the distribution of tight junction proteins Occludin and ZO-1 and down-regulating the expression of MLCK in colonic epithelial cells. These findings suggest that Wuji Wan may remit IBS by modulating the gut microbiota and stabilizing the gut mucosal barrier, indicating that the use of a classical formula of Traditional Chinese Medicine (TCM) that exhibits a prebiotic effect may be a promising strategy for PI-IBS treatment.